Three-fiber optical probe for studying fluidized gas-solid beds in bubbling regime. (2011)
This work shows the development of a three-optical fi ber probe to study the behavior of the bubble in bubbling fluidized gas-solid beds. Its compact design allows minimizing disturbance to the fl ow fi eld, resulting in more accurate results than other probes. Bubbling fl uidized beds are widely used in petrochemical processes, metallurgical, and thermoelectric plants. The behavior of the bubble is one of the most important parameters for the simulation and design of thermoelectric reactors, as it relates to the jumping phase, the interaction between solid and gaseous phases of the bed, and the behavior of mass transfer. Knowing both the speed and the size of the bubble helps to characterize these systems, bringing about a better design of large-scale reactors.